EFL STUDENTS’ PERSPECTIVE ON WHATSAPP AS MEDIA OF ONLINE TEACHING AND LEARNING IN COVID-19 PANDEMIC - Arsyada Nihayati; Lilia Indriani (Universitas Teknokrat Indonesia, 2021)
The COVID-19 Pandemic indicated a unique challenge to the educational system. The Centers for Disease Control and Prevention recently advised doing social distancing. Many applications were developed and web-based. One of them was developed and become famous was WhatsApp. WhatsApp is one of the mobile phone applications and web-based social network that integrates with various features used to communicate with other users, ranging from education, business, and entertainment developed this social networking site. This study aimed to explore the EFL student’s perspective on WhatsApp as media on teaching and learning during this Pandemic. This paper used a qualitative descriptive method. The data was collected through questionnaire and call interview. After the research is conducted, we will find out how EFL students perspective WhatsApp as an online teaching-learning media during a pandemic.